Integrasi Majelis Sholawat Banjari dalam Kegiatan Keagamaan - Aprilia, Nurul Fitria (Proceedings of Annual Conference for Muslim Scholars, 2024)
This study explores the role of banjari in religious activities in Ketawang village, Purwoasri sub-district, Kediri district and its impact on social harmony and community spirituality. Banjari is a youth group that chants shalawat, prayers and religious songs that plays an important role in organizing and implementing religious events in this village. The urgency of this research lies in the need to understand the social and religious dynamics that can contribute to increasing the capacity of the community in the face of changing times. Qualitative research methods were used to collect data through interviews, observation and documentation. The results show that banjari not only functions as an event organizer but also as a connecting tool that strengthens social ties in a community. The religious activities they organize involve various levels of society, creating a space for deep social interaction and strengthening relationships between residents. In addition, these activities also have a positive effect on individual spirituality. This study concludes that the integration of religious activities through Majelis Sholawat Banjari contributes significantly to the harmony and spirituality of the Ketawang Village community, creating a harmonious social environment and improving individual spirituality.